Jesus and his world : the archaeological evidence - Evans, Craig A. (2013)
A world-renowned scholar explores the latest archaeological evidence about the historical Jesus and His world. -- Book Cover.
In the shadow of Sepphoris : growing up in Nazareth -- Among the devout : religious formation in the synagogue -- In the books : reading, writing and literacy -- Confronting the establishment : ruling priests and the temple -- Life with the dead : Jewish burial traditions -- Have we found the family tomb of Jesus? -- What did Jesus look like? -- Questions for discussion and reflection.
Includes bibliographical references and index.
Keywords: Jesus Christ; Bible. -- Antiquities